Uterine Transplantation In Islamic Jurisprudence: Balancing Medical Needs And Shariah Boundaries - Husna Balqis Mohd Azamuddin; Che Anis Shaqeera Che Zulkifli; Nurzaliffa Saffiya Ismail; Nurul I’lya Maisarra Mohd Raffe; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
Advances in medical technology have opened the door to various methods of fertility treatment, including uterine organ donation and transplantation as an alternative for women suffering from problems such as the absence or damage to the uterus. However, this issue raises various ethical questions and syariah law related to nasab, the protection of women’s dignity and the need for offspring. This study also aims to examine the hukm of donation and uterine transplantation according to an Islamic perspective, focusing on analysing the results of the National Muzakarah Fatwa and the views of contemporary and classical scholars. The results of the study show that the original law of donation and uterine transplantation is haram and should not be re-examined for basic needs (daruriyyat) for women who suffer from infertility problems or the absence of a uterus to get descendants. This study has proved that there is no confusion of nasab and violation of the principles of maqasid shariah. Therefore, this study suggests that the method of uterine transplantation is accepted in Malaysia and is in line with the development of medical science and technology, as in other developed Islamic countries.